Multiculturalism Of Fear Etnis Tionghoa Pada Pemilihan Presiden Tahun 2019 - Davtywa, Daffa; Maryanah, Tabah; Kurniawan, Budi (Government Science Department , Faculty of Social and Political Science - University of Lampung. Journal of Government and Social Issues (JGSI), 2021)
The 2019 Presidential Election in Dusun Kebun Sayur Desa Mengkubang, Belitung Timur resulted in Jokowi-Maruf Amin coming out as the winners. The percentage of votes in Dusun Kebun Sayur, Jokowi-Maruf Amin got 80.05% and Prabowo-Sandiaga Uno got 19.95%. One of the biggest votes in Jokowi’s victory came from the Chinese Ethnic group. The purpose of this research is to explain why the Ethnic Chinese in Dusun Kebun Sayur choose the Jokowi-Maruf Amin in the 2019 Presidential Election and to find out if there is true a fear of Ethnic Chinese who will be threatened if the Prabowo is elected president. The theory used in this study is Multiculturalism of Fear (Jacob Levy, 2000). This study used descriptive qualitative method. The data collection techniques used in this study is interviews and documentation. The results of this study showed that the majority of Ethnic Chinese in Dusun Kebun Sayur chose Jokowi-Maruf Amin because of fears about Parbowo's if elected President of Republic of Indonesia. Based on the findings in the field, the Ethnic Chinese fear towards Prabowo because they claimed that Prabowo was the figure responsible for the 1998 riots, this caused Ethnic Chinese trauma to prabowo. On the other side, They are also afraid of Prabowo's supporters who consist of hard-line Islamic groups like FPI. This caused to majority of the Chinese Ethnic in Dusun Kebun Sayur in 2019 presidential election to dominate Jokowi and Maruf Amin.